Editorial - Mendes, Deise Maria Leal Fernandes; Soares, Adriana Benevides; Tsallis, Alexandra Cleopatre; Feijoo, Ana Maria Lopez Calvo de; Mancebo, Deise; Barros, Rita Maria Manso de (Estudos e Pesquisas em Psicologia, 2012)
Deise Maria Leal Fernandes Mendes, Adriana Benevides Soares, Alexandra Cleopatre Tsallis, Ana Maria Lopez Calvo de Feijoo, Deise Mancebo, Rita Maria Manso de Barros